2011
DOI: 10.1038/nm.2590
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of ligand receptor binding with Gaussia luciferase complementation

Abstract: Studies of ligand-receptor binding and development of receptor antagonists would benefit greatly from imaging techniques that translate directly from cell-based assays to living animals. We used Gaussia luciferase protein fragment complementation to quantify binding of chemokine CXCL12 to receptors CXCR4 and CXCR7. Small molecule inhibitors of CXCR4 or CXCR7 specifically blocked CXCL12 binding in cell-based assays, and these studies revealed differences in kinetics for inhibiting chemokine binding to each rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 27 publications
2
73
0
Order By: Relevance
“…Breast cancer cells can express both of the CXCL12/SDF-1 receptors, CXCR4 and the alternative inhibitory receptor CXCR7 (48). To confirm POL5551’s specificity for CXCR4 over CXCR7, we utilized a complementation-imaging model (35), in which the N terminal portion of the Gaussia luciferase (GLuc) is fused to CXCR4 or CXCR7 while the C terminal portion of GLuc is fused to the ligand SDF-1. In the presence of coelenterazine, reconstitution of GLuc and subsequent light production serves as a quantitative measure of receptor-ligand binding and POL5551 bioactivity (Supplemental Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer cells can express both of the CXCL12/SDF-1 receptors, CXCR4 and the alternative inhibitory receptor CXCR7 (48). To confirm POL5551’s specificity for CXCR4 over CXCR7, we utilized a complementation-imaging model (35), in which the N terminal portion of the Gaussia luciferase (GLuc) is fused to CXCR4 or CXCR7 while the C terminal portion of GLuc is fused to the ligand SDF-1. In the presence of coelenterazine, reconstitution of GLuc and subsequent light production serves as a quantitative measure of receptor-ligand binding and POL5551 bioactivity (Supplemental Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…CXCL12-CGLuc, NGLuc-CXCR4, and NGLuc-CXCR7 MDA-MB-231 cells were generated as previously described (35). …”
Section: Methodsmentioning
confidence: 99%
“…As the physical phantom was turned and imaged, it was shown that the maximum intensity in images decreased dramatically as a function of angle, and it is seen that there is a 10-fold drop in total top-view intensity in images over the range in which the majority of the flux was physically visible (sets 1 to 5). This is a dramatic change given that this method is presently used for quantification in biomedical studies [1,3,30] and the actual surface flux was the same in each case. Applying backprojection did not improve results, but when applying the proposed method the reconstructed flux was stable as a function of angle.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, they quantified the binding of chemokine (C-X-C motif) ligand 12 (CXCL12) to chemokine (C-X-C motif) receptors 4 (CXCR4) and 7 (CXCR7). BLI showed CXCL12-CXCR7 binding in primary and metastatic tumors in a mouse model of breast cancer and enabled them to quantify the drug-mediated inhibition of CXCL12-CXCR4 binding in living mice [79]. …”
Section: Reporter Genes For Bioluminescence Imagingmentioning
confidence: 99%